TANGGUANG JAWAB CENDEKIA MUSLIM TERHADAP PERKEMBANGAN KEILMUAN ISLAM - J Sutarjo (Postgraduate State Islamic Institute (IAIN) Metro, 2014)
Science serves as a tool to dissect unknown fenoma nature to humans, so it takes a maximum sense of empowerment. Sense of empowerment to the maximum, then the new knowledge about the nature and its contents can be created. To given the importance of science to man, the human should strive to continue in discovering and developing the existing science, because the science is existed to provide a satisfying life, lift status and dignity as well as to establish a well-developed civilization that will be remembered by history. In line with the times, especially with the advent of globalization, the scientific world we experience many challenges, both internal and external challenges. Internal challenges come from Muslim intellectuals we are not able to create new science, making it less able to